Quad-Band Multiport Rectenna for RF Energy Harvesting in Ambient Environment - Sunanda Roy; R. Jun-Jiat Tiang; Mardeni Bin Roslee; Md. Tanvir Ahmed; M. A. Parvez Mahmud (IEEE Access)
This article proposes a quad-band multiport harvester that can scavenge ambient radio frequency (RF) energy of available frequency bands (i.e. GSM-900, GSM-1800, 3G and Wi-Fi) efficiently. This design’s novelty is the use of frequency-dependent multiple antenna ports that enables the harvester to fully exploit all available frequency bands, spatial diversity, and polarization for maximizing the harvested RF energy at a lower power density level in an ambient environment. Indistinctly, the proposed antenna consists of 8-port which maintain $0.33λ × 0.33λ $ (i.e. wavelength $λ $ calculated at 0.9 GHz in free space) average area per port and has achieved more than 35% relative bandwidth (BW) with a maximum gain of 6.5 dBi to cover the selected frequency bands. Besides, the proposed quad-band rectifier with a multi-stub impedance matching network is feasible for RF harvesting over the available ambient frequency bands. The proposed rectenna’s measurement results show that the generated average dc output voltage is increased up to 0.750 V at a low RF input power density of −27 dBm for a load resistance of 2.11 $\text{k}Ω $ . The overall dc rectification efficiency of the 8-port pixel harvester is also assessed and depicted to be 66.52% when the resultant RF input power density level is −27 dBm. Measurement in an ambient outdoor and controlled indoor environment is also conducted, demonstrating that the new 8-port pixel RF harvester can produce a dc output voltage of 0.797 V which is greater than some of the reference RF harvesters.